(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
A large number and variety of works on the study of genes, controlling the activity of cytokines, confirms the relevance and the prospects of this direction in identifying predisposition, study of the mechanisms of development and course of periodontal diseases. It is known that the effect of cytokines on target cells in tissues periodontal can determine the features of the histopathological picture. The most important properties of IL-1 - stimulation of proliferation antigen-preactivated mature T-lymphocytes, increased production IL-2, IL-4, TNFα, stimulation of phagocytosis - well known and widely highlighted in the literature. The main cells producing IL-1, TNFα, IL-4 in the body are monocytes / macrophages, as well as T- and B-lymphocytes, neutrophilic leukocytes, endothelial cells.